Mechanics of Hsp70 chaperones enables differential interaction with client proteins - Schlecht, Rainer; Erbse, Annette; Bukau, Bernd; Mayer, Matthias P. (Nature structural & molecular biology, 2011)
Hsp70 chaperones interact with many proteins through a substrate-trapping mechanism that requires ATP. Hsp70s have a lid over the substrate-binding cleft, whose function is controversial. Using cysteine cross-linking and EPR in the Escherichia coli Hsp70 DnaK, it is now shown that helix B of the lid subdomain can adopt three major conformational states and that it does not necessarily close over bound substrates, allowing binding of natively folded states.